2015
DOI: 10.1093/annonc/mdu507
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian network meta-analysis comparing concurrent chemoradiotherapy followed by adjuvant chemotherapy, concurrent chemoradiotherapy alone and radiotherapy alone in patients with locoregionally advanced nasopharyngeal carcinoma

Abstract: No significant improvement was found following CCRT + AC compared with CCRT alone. Whether the omission of additional AC can reduce toxic effects without adversely affecting survival in patients with locoregionally advanced NPC should be further explored, in addition to the precise patient status that would benefit from AC following CCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 27 publications
1
72
0
Order By: Relevance
“…Additional information is anticipated from a recently completed multicentre randomised trial (NCT00677118) comparing CRT-A and CRT. Long-term outcomes of the Chen 2012 study are also due to be reported [44].…”
Section: Discussionmentioning
confidence: 99%
“…Additional information is anticipated from a recently completed multicentre randomised trial (NCT00677118) comparing CRT-A and CRT. Long-term outcomes of the Chen 2012 study are also due to be reported [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC), derived from the epithelial cells located in nasopharynx, displays a significant geographic distribution that with the highest incidence in Southern China and Southeast Asia [1,2]. Although the advance in radiotherapy techniques and chemotherapy regimens has markedly improved the local control of NPC [3], there are still some unknown reasons to hamper the treatment progress of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Although the advance in radiotherapy techniques and chemotherapy regimens has markedly improved the local control of NPC [3], there are still some unknown reasons to hamper the treatment progress of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…NPC is also highly chemosensitive; therefore, many randomised trials have investigated the efficacy of combining chemotherapy with primary radiotherapy in the past two decades [3]. Concurrent chemoradiotherapy, with or without adjuvant chemotherapy, is the most efficacious [4][5][6], and is now the standard treatment for stages IIB and advanced disease. The addition of neoadjuvant chemotherapy is promising, and the results of phase III trials are awaited [7].…”
mentioning
confidence: 99%